Petri net approach to the synthesis of self-reprogramming control software - Banaszak, Zbigniew; Wójcik, Robert; D'Souza, Kelwyn A. (Zielona Góra: Uniwersytet Zielonogórski)
A new approach to automated design of adaptive concurrent control software of discrete event systems is presented. An algorithm transforming a given specification of the pipeline-like flowing concurrent processes into a Petri net model of admissible control flows of competing processes is introduced. Models generated guarantee the time-independent and deadlock-free execution of processes.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka